Psoriasis severity: commonly used clinical thresholds may not adequately convey patient impact. (9th December 2020) - Golbari, N.M.; van der Walt, J.M.; Blauvelt, A.; Ryan, C.; van de Kerkhof, P.; Kimball, A.B.
Abstract: Background: Psoriasis severity is usually evaluated using quantitative and qualitative measures, including per cent body surface area (BSA) involvement, the Psoriasis Area and Severity Index (PASI) and the Dermatology Life Quality Index (DLQI), a patient‐reported questionnaire. However, standardized definitions for psoriasis severity categories have not been well established. A PASI of 10 or 12 has remained the minimal severity threshold defining eligibility for psoriasis treatments. In the present study, the validity of this cut‐off was re‐evaluated in the context of quality of life. Objective: To determine whether the thresholds commonly used to define moderate psoriasis (PASI of 10–12 and BSA of 10) are supported by patient‐reported DLQI data. Methods: A systematic review of randomized controlled trials that enrolled mild or moderate patients published between January 2000 and June 2017 was used to assess correlations between provider and patient‐generated severity at baseline. Results: For subject groups with high impact on quality of life (DLQI > 10), the mean weighted BSA was 7.6 (Range: 7.1–8.4) and the mean weighted DLQI was 11 (Range: 10.2–12.2). Similarly, the mean weighted PASI for patients with DLQI > 10 was 8.7 (Range: 7.1–10.1) and the mean weighted DLQI was 10.9 (Range: 10.1–12.2). Conclusion: Patients with PASI or BSA scores less than 10 can have major quality of life impairment. In general, the objective measures of BSA and PASI alone, when excluding DLQI, may not fully capture the impact of disease severity.